2005
DOI: 10.1145/1113847.1113893
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a core literature for computing education research

Abstract: After four decades of research on a broad range of topics, computing education has now emerged as a mature research community, with its own journals, conferences, and monographs. Despite this success, the computing education research community still lacks a commonly recognized core literature. A core literature can help a research community to develop a common orientation and make it easier for new researchers to enter the community. This paper proposes an approach to constructing and maintaining a core litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…The work by Fincher & Petre [21], Pears et al, [41] and Seidman et al, [46] on discipline formation are good examples of CS Ed Research defining itself as a 'discipline', distinct from both the Education and CS disciplines, though cognate with CS and integral to quality CS education. Thus CS Ed Research can contribute to a vibrant teaching-research nexus in CS Education.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work by Fincher & Petre [21], Pears et al, [41] and Seidman et al, [46] on discipline formation are good examples of CS Ed Research defining itself as a 'discipline', distinct from both the Education and CS disciplines, though cognate with CS and integral to quality CS education. Thus CS Ed Research can contribute to a vibrant teaching-research nexus in CS Education.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore they are inherently not trans-disciplinary, and tend to be restrictive of the scholarship of integration. Fortunately for educators in the computing field, there is a developing sub-discipline of CS Ed research [21,41], which is congruent with many aspects of the practicing CS educator's computing discipline focus.…”
Section: Disciplinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally the papers were classified using a previously published taxonomy, and citation information collected using Google Scholar. A taxonomic breakdown of the papers finally selected is presented using a modified version of the Lisbon taxonomy [74] The annotated bibliography comprises 45 papers selected from the nominations. In selecting papers the following criteria were applied.…”
Section: Areamentioning
confidence: 99%
“…Limitations and areas of incomplete coverage of existing research efforts are also identified. The analysis applies publication and research quality metrics developed by a previous ITiCSE working group [74]. …”
mentioning
confidence: 99%